Need to proof using laws

$$\lnot(p \land \lnot q) \lor q \equiv \lnot p \lor q$$

$\lnot(p \land \lnot q) \lor q$

$\equiv (\lnot p \lor \lnot(\lnot q)) \lor q\quad$ First De Morgan's law

$\equiv (\lnot p \lor q) \lor q \quad$ Double Negation

I think I have the first to laws right. What else do I need to do to prove the equivalence?


1 Answer 1


Yes, you've done fine. Now use the associative law to get $$(\lnot p \lor q) \lor q \equiv \lnot p \lor(q \lor q) \equiv \lnot p \lor q$$

You can call the reason for the last equivalence "repetition" (1): $$q \lor q \equiv q\tag{1}$$ $$q \land q \equiv q\tag{2}$$

  • $\begingroup$ Idempotence is another name for the ((q∨q)≡q) law. $\endgroup$ Sep 18, 2014 at 19:43

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.